Pablo Picasso, art thief: the “affaire des statuettes” and its role in the foundation of modernist painting - Charney, Noah (Arte, Individuo y Sociedad, 2014)
When the Mona Lisa was stolen in 1911 by the Italian handyman Vincenzo Peruggia, both Pablo Picasso and Guillaume Apollinaire were brought in by the Paris police for questioning. They were innocent of having stolen the Mona Lisa, but they were in fact guilty of having stolen other art from the Louvre—for in Picasso’s dresser lay hidden several ancient Iberian statue heads that had been stolen from the Louvre in 1907 by Apollinaire’s secretary, Honore-Joseph Gery Pieret, almost certainly on commission from Picasso himself, who may also have assisted in the theft. Picasso’s involvement in art theft is little known, even though the so-called “affaire des statuettes” made international headlines in 1911. The theft did influence Picasso’s art and rise of Modernism, for the stolen statue heads were integrated into Picasso’s famous paintings, Les Demoiselles d’Avignon (1907), which is widely considered to be the first great work of Modernism. This article tells the complete, true story of Picasso and Apollinaire’s involvement in art theft, and the “affaire des statuettes.”